Work Ability Index (WAI) values in a sample of the working population in Poland - Grzegorz Juszczyk; Aleksandra Izabela Czerw; Urszula Religioni; Dominik Olejniczak; Jolanta Walusiak-Skorupa; Tomasz Banas; Marcin Mikos; Anna Staniszewska (Annals of Agricultural and Environmental Medicine, 2019)
Introduction Ability to work is most often defined as a relationship between a person’s resources and requirements specific to a particular type of work. It is the result of interaction between job requirements in terms of physical and mental strain, capabilities and skills of the employee, as well as his/her health condition and own evaluation of functioning in a given organizational and social situation.